A comprehensive analysis of the limitations of the shift to virtual learning in universities and colleges during COVID-19 in developing nations (Research, Society and Development, 2024)
This literature review aims to discuss the transition to online distance learning during the Corona Virus Disease (COVID-19) pandemic in universities and colleges in underdeveloped nations. The limits and potential possibilities identified by the systematic review methodology were used to guide future practices in online distance learning. The results highlight several drawbacks, including digital inequality, inconsistent internet connectivity, a lack of technology proficiency and preparation among teachers and pupils, and a shortage of digital solutions. The results also show that the majority of students had social and emotional difficulties as a result of their quick and careless switch to online distance learning. It was determined that, even before the COVID-19 epidemic, the majority of the restrictions were caused by a deficiency of digital culture. Further possible areas for research recommended in this paper include the exploration of digital inclusion among marginalized groups in developing countries.